Building International Cooperation in Utilizing the Internet of Things (Iot) for Defense: Towards Better Global Security - Adestria, Elga; Almubaroq, Hikmat Zakky (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The digital Era has a fairly rapid development, in the era of Industry 4.0, the defense industry donated by manufacturing companies is driven by the presence of information and Communication Technology. The Internet of Things (IoT) has become one of the key factors in the transformation of the global industry. This research was conducted using qualitative methods with a literature review approach. The results and analysis are carried out by absorbing various literature such as books, journals, articles, news, online documents, internet related to the research topic which are then extracted, filtered with the aim of evaluating the information based on predetermined criteria. The role of international cooperation in improving IoT security is very complex, it includes several important aspects. First, international cooperation can facilitate the exchange of information about security threats and best practices between countries. With a broad range of knowledge and experience, countries can learn from each other and develop more effective strategies in addressing IoT security risks. Conclusion as of this writing, with international cooperation and strong standardization, companies can prioritize security in IoT implementation to reduce the risk of data breaches and breaches, and create a more secure and trustworthy environment for IoT utilization in a global context.